2017
DOI: 10.1589/jpts.29.1292
|View full text |Cite
|
Sign up to set email alerts
|

The effects of aroma massage and foot bath on psychophysiological response in stroke patients

Abstract: [Purpose] This research aimed to examine the effects of back massage and foot bath with blended essential oil on psychophysiological response in stroke patients. [Subjects and Methods] The subjects were 14 adult stroke patients randomly divided into the experimental group (7 patients) and the control group (7 patients). Physical and psychological stress, mood state and sleep satisfaction was measured using evaluation instruments and body temperature was measured with infrared thermography (T-1000). [Results] M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…Experiments have shown these herbal formulas can modulate PGE 2 and PGE 2α production, block calcium channel and COX-2, increase the expression of nitric oxide and its synthetase, downregulate the contents of oxytocin, vasopressin, endothelin-1, and malondialdehyde, reverse the increased superoxide, and decrease the levels of interleukin-6, tumor necrosis factor-2α, whole blood viscosity, and plasma viscosity [25][26][27][28][29][30]. Further, footbaths can also improve microcirculation and increase skin permeability to enhance the absorption of TCM herbal formulas and their active compounds [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have shown these herbal formulas can modulate PGE 2 and PGE 2α production, block calcium channel and COX-2, increase the expression of nitric oxide and its synthetase, downregulate the contents of oxytocin, vasopressin, endothelin-1, and malondialdehyde, reverse the increased superoxide, and decrease the levels of interleukin-6, tumor necrosis factor-2α, whole blood viscosity, and plasma viscosity [25][26][27][28][29][30]. Further, footbaths can also improve microcirculation and increase skin permeability to enhance the absorption of TCM herbal formulas and their active compounds [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…An example is a study that assessed the effect of massage and foot baths on psychophysiological responses of patients with stroke. This study showed that patients assigned to the experimental group had greater satisfaction towards their treatment and better temperature balance between both sides of the body 43 . Zanona et al investigated this subject when they combined Occupational Therapy and Virtual Reality for treating functionality and body temperature of patients with stroke sequelae 44 .…”
Section: Discussionmentioning
confidence: 67%
“…The PRISMA diagram ( Figure 1 ) summarizes the results of the scientific literature search and 18 randomized controlled trials were included [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. No author responded when contacted for additional information.…”
Section: Resultsmentioning
confidence: 99%